Desempenho escolar e bullying em estudantes em situação de vulnerabilidade social - Zequinão, Marcela Almeida (2017)
Introduction: School bullying is characterized by over time repetitiveness of aggression, by the intentional injuring or causing suffering to another, and by the imbalance of power between the participants. This is not a new phenomenon, because the recurring situation of violence between peers at school has probably been a regular feature throughout human history. Involvement in school bullying can have negative consequences, including for the students´ teaching-learning process, in which those involved may have troubles such as failing, dropping out, as well as episodes of indiscipline. Objective: Identify the school performance of children and adolescents in a socially vulnerable situation, as well as to analyse the possible relationships of this performance with participation in the situations of violence that characterize school bullying. Method: 375 primary school children and adolescents of both genders aged between 8 and 16 years participated in the study. The instruments used were School Performance Test, Sociometric Scale and, Questionnaire for the Study of Violence Among Peers. The data were analysed using ANOVA Two-way test and Spearman correlation. Results: The present study indicates that children and adolescents in a socially vulnerable situation had results that were below expectations with respect to school development and performance in the three subtests – writing, arithmetic, and reading – in both genders and in different age groups. In an intra and extra analysis group, there was a significant difference between female children and adolescents in all subtests. However, the same was not observed among boys. There was also a relationship between poor school performance and participation in bullying situations, in which it was found that the score on the writing subtest was negatively correlated with practicing aggression and witnessing violence at school. A similar result occurred in relation to the reading subtest. The arithmetic subtest score, in turn, correlated negatively with the three forms of participation in situations of school violence: to assault, suffer abuse, and witnessing violence against colleagues. Finally, the total score obtained in SPT negatively and significantly correlated with practicing aggression and witnessing violence. Conclusion: Based on the results of this study, it was found that most children and adolescents in a socially vulnerable condition showed a lower school performance level than expected for their year attending. Allied to these results, it was found that teenage girls showed better performance than children of the same gender did. Moreover, there is a relationship between poor school performance and participation in bullying situations in different roles: victim, bully, and bystander.